Genome assembly of Stephania longa provides insight into cepharanthine biosynthesis - Shang, Huiying; Lu, Yuan; Xun, Lulu; Wang, Kun; Li, Bin; Liu, Yuxuan; Ma, Tao (Frontiers in Plant Science, 2024)
Introduction Stephania longa, a medicinal plant renowned for producing cepharanthine, has gained significance due to the compound's notable antiviral properties against SARS-CoV-2. However, a comprehensive genetic understanding of S. longa has been lacking. This study aimed to develop a high-quality, chromosome-level genome assembly to uncover the genetic intricacies and evolutionary narrative of this species. By integrating genomic data with metabolomic and transcriptomic analyses, we sought to identify key genes involved in cepharanthine biosynthesis. Methods We employed a multi-faceted approach comprising genome assembly, phylogenetic analysis, gene family dynamics investigation, metabolomic profiling, and gene expression analysis across various tissues of S. longa. This integrated strategy enabled the identification of key genes involved in cepharanthine biosynthesis and elucidated the species’ evolutionary history. Results Our phylogenetic analysis clarified the placement of the genus Stephania within the Ranunculales order and revealed its notably high mutation rate. We identified gene family expansions and signs of positive selection likely contributing to Stephania’s unique metabolic capabilities. Metabolomic profiling uncovered complex regulatory mechanisms orchestrating the biosynthesis and distribution of cepharanthine and related metabolites. Through the integration of genomic, transcriptomic, and metabolomic data, we identified genes with expression patterns and evolutionary trajectories suggesting pivotal roles in cepharanthine biosynthesis, including those involved in crucial biosynthetic steps. Discussion This comprehensive study, integrating genomic, metabolomic, and transcriptomic approaches, provides valuable insights into S. longa's biosynthetic potential. It not only enhances our understanding of the species but also establishes a foundation for future investigations into the biosynthesis and therapeutic exploitation of cepharanthine and related alkaloids.